2017
DOI: 10.1177/0276146717723964
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated Consumer Guilt

Abstract: This study considers fair-trade as a collaborative strategy of dealing with the wicked problem of apparel sweatshops. The study assumes that consumer guilt increases the market share of fair-trade products which can be regarded as a favorable change in the marketing system’s output. The paper develops and validates a model of guilt-induced fair-trade buying based on this notion. The model comprises negative affect, ethical judgment, and self-efficacy as antecedents of anticipated consumer guilt. The study’s re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…This is close to the concepts of both social responsibility guilt (Burnett & Lunsford, 1994), and guilt related to others (Dahl et al, 2003), defined as the emotional reaction resulting from consumption that violates perceived social obligations towards society (namely family, other citizens, or the environment). Existing research has shown that stressing the negative consequences to other people of a given consumption behavior (Antonetti & Maklan, 2014; Lindenmeier et al, 2017; Steenhaut & Van Kenhove, 2006) and activating consumer self‐accountability (Peloza et al, 2013) stimulates anticipated feelings of guilt, thus increasing consumers’ ethical intentions, such as the preference for products with ethical attributes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is close to the concepts of both social responsibility guilt (Burnett & Lunsford, 1994), and guilt related to others (Dahl et al, 2003), defined as the emotional reaction resulting from consumption that violates perceived social obligations towards society (namely family, other citizens, or the environment). Existing research has shown that stressing the negative consequences to other people of a given consumption behavior (Antonetti & Maklan, 2014; Lindenmeier et al, 2017; Steenhaut & Van Kenhove, 2006) and activating consumer self‐accountability (Peloza et al, 2013) stimulates anticipated feelings of guilt, thus increasing consumers’ ethical intentions, such as the preference for products with ethical attributes.…”
Section: Resultsmentioning
confidence: 99%
“…Individuals with high proneness to ethics and sustainability guilt are expected to try to avoid the personal negative experience associated with consumption behaviors that create damage to other people and/or the environment. Research has shown that anticipated guilt affects sustainable (Onwezen et al, 2014) and socially responsible (Lindenmeier et al, 2017) consumer behavior. Hence, we hypothesize that ethics and sustainability guilt proneness has a positive impact on environmentally conscious consumer decision‐making (H3.1).…”
Section: Phase 3: Test–restest Reliability and Nomological Validitymentioning
confidence: 99%
“…Additionally, as it relates to advertisements promoting a cause–company partnership, guilt appeals appear to be more effective than neutral advertising (Chang, 2011). Additional prosocial behavior such as recycling behavior and the purchase of fair‐trade products are similarly influenced by guilt (Lindenmeier et al., 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Anticipated consumer guilt arises within the process of self-realization and was found to mediate the effects of its antecedents on FT buying intention with FT consumers scoring higher in the social factor. Anticipated consumer guilt consists of two components: “negative affect and self-directed ethical judgment” (Lindenmeier et al, 2017). Finally, self-efficacy was proven to have “direct positive effects on anticipated consumer guilt and fair-trade buying behavior” (Lindenmeier et al, 2017, p. 9).…”
Section: Thematic Reviewmentioning
confidence: 99%
“…Anticipated consumer guilt consists of two components: “negative affect and self-directed ethical judgment” (Lindenmeier et al, 2017). Finally, self-efficacy was proven to have “direct positive effects on anticipated consumer guilt and fair-trade buying behavior” (Lindenmeier et al, 2017, p. 9). We have identified the above relationships in a network in Figure 4.…”
Section: Thematic Reviewmentioning
confidence: 99%